Identification of the Kombucha consumer profile in Fortaleza-CE - Macedo Dantas Coelho, Raquel; Almeida, Aryelle; Jair Wurlitzer, Nédio; Machado Sousa, Paulo Henrique (Nutrivisa Revista de Nutrição e Vigilância em Saúde, 2023)
Made from the fermentation of sweetened tea from the Camellia sinensis herb by a symbiotic culture of bacteria and yeasts, Kombucha has been gaining ground in the Brazilian and international scene for its benefits and its possible ability to assist in human well-being. This fermented beverage has shown significant growth in the beverage market and, because of this, the present work aimed to carry out a data survey on the set of behavioral characteristics of kombucha consumers in the city of Fortaleza-CE and metropolitan region and the relationship of these individuals with the drink; as well as identifying the attributes that influence the purchase decision and prospecting the population’s acceptability for fermented beverages such as kombucha. To carry out the research, the Google forms platform was used, and these forms were distributed through social networks following the snowball technique. XLSTAT software, Maxdiff test and Excel were used for data analysis. Thus, it was found that most kombucha consumers are women, young people, with an income between 1 and 4 minimum salary, single, with higher education and residents of the noblest areas of the city. The attributes that were considered decisive for the purchase decision were: health benefits, probiotic, flavor, increase immunity, contain no chemical additives and high antioxidant content. In this way, it is expected that this study will contribute with a direction to kombucha producers for the elaboration of new products directed to a specific public.